The political economy of sugar-sweetened beverage taxation in Latin America: lessons from Mexico, Chile and Colombia - Angela Carriedo; Adam D. Koon; Luis Manuel Encarnación; Kelley Lee; Richard Smith; Helen Walls (BMC, 2021)
Abstract Background In Latin America, total sales of sugar-sweetened beverages (SSBs) continue to rise at an alarming rate. Consumption of added sugar is a leading cause of diet-related non-communicable diseases (NCDs). Coalitions of stakeholders have formed in several countries in the region to address this public health challenge including participation of civil society organizations and transnational corporations. Little is currently known about these coalitions - what interests they represent, what goals they pursue and how they operate. Ensuring the primacy of public health goals is a particular governance challenge. This paper comparatively analyses governance challenges involved in the adoption of taxation of sugar-sweetened beverages in Mexico, Chile and Colombia. The three countries have similar political and economic systems, institutional arrangements and regulatory instruments but differing policy outcomes. Methods We analysed the political economy of SSB taxation based on a qualitative synthesis of existing empirical evidence. We identify the key stakeholders involved in the policy process, identified their interests, and assess how they influenced adoption and implementation of the tax. Results Coalitions for and against the SSB taxation formed the basis of policy debates in all three countries. Intergovernmental support was critical to framing the SSB tax aims, benefits and implementation; and for countries to adopt it. A major constraint to implementation was the strong influence of transnational corporations (TNCs) in the policy process. A lack of transparency during agenda setting was notably enhanced by the powerful presence of TNCs. Conclusion NCDs prevention policies need to be supported across government, alongside grassroots organizations, policy champions and civil society groups to enhance their success. However, governance arrangements involving coalitions between public and private sector actors need to recognize power asymmetries among different actors and mitigate their potentially negative consequences. Such arrangements should include clear mechanisms to ensure transparency and accountability of all partners, and prevent undue influence by industry interests associated with unhealthy products.